Baseline assessment report for the Occupied Palestinian Territories (OPT) pilot sites in Wadi Al-Fari’a in the West Bank - Belhaj Fraj, Makram; Rabi, A.; Murrar, A.; Samhan, S.; Fragaszy, Stephen; Ruckstuhl, Sandra; Abdelwahab, Noura; Samarasekara, Vidhisha (International Water Management Institute, 2025)
This baseline study draws on Resilient Nature-Based Water Solutions (RNBWS) pilot interventions undertaken by the Al Murunah project in the upper catchment of Wadi Al-Fari’a, specifically in the communities of Ras Al-Fari’a, Wadi Al-Fari’a, and the Fari’a Refugee Camp in the Occupied Palestinian Territories (OPT). It provides a detailed account of the 2023 analysis of the biophysical, socio-economic, agricultural, and policy contexts shaping the technical, social, and market design of the pilot, as well as broader project activities, including capacity building, training, and policy engagement.